2007
DOI: 10.1002/prot.21385
|View full text |Cite
|
Sign up to set email alerts
|

The N‐ and C‐termini of the human Nogo molecules are intrinsically unstructured: Bioinformatics, CD, NMR characterization, and functional implications

Abstract: RTN4 or Nogo proteins are composed of three alternative splice forms, namely 1192-residue Nogo-A, 373-residue Nogo-B, and 199-residue Nogo-C. Nogo proteins have received intense attentions because they have been implicated in a variety of critical cellular processes including CNS neuronal regeneration, vascular remodeling, apoptosis, interaction with beta-amyloid protein converting enzyme, and generation/maintenance of the tubular network of the endoplasmic reticulum (ER). Despite their significantly-different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 42 publications
4
38
0
Order By: Relevance
“…Although this domain is active, we find it to be highly flexible in an aqueous environment. Notably, other studies have found that most regions are disordered in the largest splicevariant, Nogo-A (1,192 amino acids) (14,15). Disordered structure is an interesting parallel feature between Nogo and another This article is a PNAS Direct Submission.…”
Section: Resultsmentioning
confidence: 97%
“…Although this domain is active, we find it to be highly flexible in an aqueous environment. Notably, other studies have found that most regions are disordered in the largest splicevariant, Nogo-A (1,192 amino acids) (14,15). Disordered structure is an interesting parallel feature between Nogo and another This article is a PNAS Direct Submission.…”
Section: Resultsmentioning
confidence: 97%
“…48 NMR analysis revealed that an important regulator of proliferation and apoptosis, cAMPresponsive (CRE)-binding (CREB) protein (CBP), contains an intrinsically disordered ACTR-binding domain (residues 2059-2117) that completely folds upon binding. 49 Combined experimental and computational analysis revealed that N-and C-terminal regions of the human Nogo proteins 50 and C-terminal domain of a mitochondrial pro-apoptotic protein ARTS 51 are typical IDPRs, and that the prostate apoptosis response factor-4 (PAR-4), 52 prostate-associated gene 4 (PAGE4) protein, 53 and important oncoprotein c-Myc 54 are mostly disordered apoptosis-related proteins.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there is only fragmented data on this aspect. For instance, the implication of the six cysteine residues in the folding of bacterial-overexpressed soluble large extramembrane domain located at the N terminus of human RTN4A has been studied using CD and NMR spectroscopies [8,21]. The results showed that two cysteine residues (Cys699 and Cys912) out of the six, are not involved in a structurally disulfide bound.…”
Section: Structure Of Rtn Proteinsmentioning
confidence: 97%
“…For instance, AtRTNLB19 contains a 3b-hydroxysteroid dehydrogenase isomerase domain that functions in vitro as a 3b-hydroxysteroid dehydrogenase/C-4 decarboxylase activity when the RHD has been removed [7]. Beside the structured sequences, the C- and/or N-terminal domains can be highly unstructured, possibly due to the presence of proline and alanine residues [8]. This property seems important to form multiprotein complexes [9], and possibly to carry out alternative functions [10] as they can fold upon binding to their partners [11].…”
Section: Structure Of Rtn Proteinsmentioning
confidence: 98%